2016
DOI: 10.1111/bjd.14727
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study investigating the metabolic activity and local cytokine profile in patients with melanoma treated with pazopanib and paclitaxel

Abstract: In this patient population pazopanib efficacy was limited. Response is associated with low M2-like macrophage density and increased expression of several chemokines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…The CXCL13:CXCR5 axis has also been implicated in the initiation and progression of other solid tumors, such as ovarian cancer, melanoma, oral squamous cell carcinoma, osteosarcoma, thyroid cancer, and neuroblastoma (133143). One interesting study showed that specific chemokine signatures may contribute to overall survival in wild-type and mutant p53 ovarian cancers, and CXCL13 was specifically associated with better overall survival (137).…”
Section: Cxcl13:cxcr5 Axis In Solid Tumorsmentioning
confidence: 99%
“…The CXCL13:CXCR5 axis has also been implicated in the initiation and progression of other solid tumors, such as ovarian cancer, melanoma, oral squamous cell carcinoma, osteosarcoma, thyroid cancer, and neuroblastoma (133143). One interesting study showed that specific chemokine signatures may contribute to overall survival in wild-type and mutant p53 ovarian cancers, and CXCL13 was specifically associated with better overall survival (137).…”
Section: Cxcl13:cxcr5 Axis In Solid Tumorsmentioning
confidence: 99%
“…An open‐label, investigator‐led pilot study by Thurneysen et al . demonstrated that while there was no objective response to combination treatment of patients with pazopanib, a multitarget tyrosine kinase inhibitor with selectivity for VEGF receptors, and paclitaxel, a microtubule‐stabilizing drug that induces mitotic arrest, there was a dramatic increase in recruitment of tumour‐associated macrophages, as well as an increase in tumour‐promoting cytokines in response to the pazopanib–paclitaxel combination treatment . The group hypothesize that macrophage‐mediated tumour cell protection may limit the efficacy of pazopanib‐induced growth inhibition and cell death, which they indicate may be overcome by targeting macrophages with compounds such as the monoclonal antibody to colony stimulating factor‐1, emactuzumab.…”
mentioning
confidence: 77%
“… 7 The chemokines they encode are secreted by macrophages for neutrophil recruitment in the presence of necrotic cells. 8 , 9 Both exert their signal through the same receptor, CXCR2. Studies have shown that high expression of these genes is associated with poor prognosis in a number of cancers, such as in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%